Distinctive epidemiologic and clinical features of common krait (Bungarus caeruleus) bites in Sri Lanka. - Ariaratnam, C; Sheriff, M; Theakston, R; Warrell, D (2008)
A prospective study was designed to define epidemiologic and clinical features of krait bites to improve diagnosis, management, and prevention. Among 762 cases of venomous snake bites admitted to 10 Sri Lankan hospitals in which the snake responsible was brought and identified, 88 (11.5%) were caused by common kraits (Bungarus caeruleus). Bites were: most frequent in September through November. Distinctive features of B. caeruleus bites (compared with bites by other species in parentheses) were bitten while sleeping on the ground, 100% (1%); indoors, 100% (49%); between 2300 and 0500 hours, 100% (3%). Only 13% of krait victims were bitten on their lower limbs (82%), only 9% had local swelling (in all cases mild) at the site of the bite (93%), 64% developed respiratory paralysis (2%), and 91% experienced (often severe) abdominal pain (10%). Case fatality was 6% (3%). This distinctive pattern of epidemiology and symptoms will aid clinical recognition (syndromic diagnosis) and prevention of krait bite envenoming.